Is there a role of pulsed electromagnetic fields in management of patellofemoral pain syndrome? Randomized controlled study at one year follow‐up. Issue 2 (12th January 2016) - Servodio Iammarrone, Clemente; Cadossi, Matteo; Sambri, Andrea; Grosso, Eugenio; Corrado, Bruno; Servodio Iammarrone, Fernanda
Abstract : Patellofemoral pain syndrome (PFPS) is a common cause of recurrent or chronic knee pain in young adults, generally located in the retropatellar region. Etiology is controversial and includes several factors, such as anatomical defects, muscular imbalance, or joint overuse. Good results have been reported with exercise therapy, including home exercise program (HEP). Joint inflammation with increase of pro‐inflammatory cytokines levels in the synovial fluid might be seen especially when chondromalacia becomes evident. Biophysical stimulation with pulsed electromagnetic fields (PEMFs) has shown anti‐inflammatory effects and anabolic chondrocyte activity. The purpose of this randomized controlled study was to evaluate if the combination of HEP with PEMFs was more effective than HEP alone in PFPS treatment. Thirty‐one PFPS patients were enrolled in this study. All patients were instructed to train with HEP. Patients in the PEMFs group associated HEP with PEMFs. Function and pain were assessed with Victorian Institute of Sport Assessment score (VISA), Visual Analog Scale (VAS), and Feller's Patella Score at baseline at 2, 6, and 12 months of follow‐up. Drug assumption was also recorded. Increase in VISA score was significantly higher in PEMFs group compared to controls at 6 and 12 months, as well as the increase in the Feller's Patella Score at 12 months. VAS score became significantly lower in the PEMFs group with respect to control group since 6 month follow‐up. Pain reduction obtained with PEMFs enhanced practicing therapeutic exercises leading to a better recovery process; this is extremely important in addressing the expectations of young patients, who wish to return to sporting activities. Bioelectromagnetics. 37:81–88, 2016. © 2016 Wiley Periodicals, Inc.